Medication Prescription Practices for the Treatment of First Episode Schizophrenia-Spectrum Disorders: Data from the National RAISE-ETP Study - Robinson, Delbert G. (Am J Psychiatry, 2014)
OBJECTIVE: Treatment guidelines suggest distinctive medication strategies for first episode and multi-episode patients with schizophrenia. How much community clinicians adjust their usual treatment regimens for first episode patients is unknown. We examined prescription patterns and factors associated with prescription choice within a national cohort of early phase patients. METHOD: Study entry prescription data (before any influence on treatment by study procedures) were obtained from 404 participants in the RAISE-ETP study, a US nationwide effectiveness study conducted at 34 community treatment centers in 21 states for patients with first episode schizophrenia-spectrum disorders. Subjects had been treated with antipsychotics for 6 months or less at study entry. RESULTS: We identified 159 subjects (39.4% of the sample) who might benefit from changes in their psychotropic prescriptions. Of these 159 subjects, 8.8% were prescribed recommended antipsychotics at higher than recommended doses, 32.1% were prescribed olanzapine (often at high doses), 23.3% more than one antipsychotic, 36.5% an antipsychotic but also an antidepressant without a clear indication, 10.1% psychotropic medications without an antipsychotic and 1.2% stimulants. Multivariate analyses found evidence for sex, age and insurance status effects on medication prescription. Racial and ethnic effects consistent with effects found in prior multi-episode studies were found in univariate analyses. There were some regional variation in prescription practices; when present, regional patterns varied across prescribing practices. Diagnosis had limited, and inconsistent, effects. CONCLUSIONS: Besides prescriber education, policy makers may need to consider not only patient factors but also service delivery factors in efforts to improve first episode prescription practices. CLINICAL TRIALS REGISTRATION: NCT01321177: An Integrated Program for the Treatment of First Episode of Psychosis (RAISE ETP), http://www.clinicaltrials.gov/ct2/show/NCT01321177